Characteristics of Local Modulation Beam Propagating through Spatial Filter System - Kewei You; Yanli Zhang; Xuejie Zhang; Jianqiang Zhu (Advances in Condensed Matter Physics)
As local defects may significantly harm beam quality and affect safe operation, a systematic analysis of the ability of a spatial filter to alleviate these adverse effects is required. Thus, the evolutional characteristics of a beam modulated by a local defect propagating through a spatial filter system at an image reply plane and a downstream plane are analyzed in detail. Modulation stripes appear at the image reply plane; these are caused by the pinhole cutoff effect. The modulation degree increases with increasing defect size. The maximum intensification factor can reach 3.2 under certain conditions. Thus, the defect size should be restricted to a reasonable size for safe operation with a specified pinhole size. Moreover, a maximal value appears at the downstream plane, and the intensity enhances with increasing defect size. To ensure beam quality, the maximum allowable defect size and angle of the spatial filter should meet special constraints. The maximum allowable defect size is calculated based on practical configuration parameters.